Luke Doyle: capstone - Doyle, Luke, artist (Colorado State University. Libraries, 2016)
The artist's statement: I choose to make utilitarian objects because I want the experience to be more than simply looking. I have made bowls, cups, and plates for the user to incorporate into their life, I hope the plates and bowls are used at every meal. I do not think you can experience these pieces fully if you have not used your hands to touch them, to feel the surface and weight and to explore then textural variation. I have used simple, utilitarian glaze design to offer a highly functional and interesting object. I used a glossy white glaze to line the interior of all the pots. The white glaze offers a rich white surface that is visually clean as well as practically easy to wash after use. I have used the unglazed clay as part of the surface because it gives the user's hand various textures to explore from glossy to matte to raw clay. Allowing the clay to show through also creates a depth of surface. The glaze is meant to be simple while allowing variation of color and texture letting the users examine the subtle color changes in the clay. My interest in pottery grew with my interest in making pottery. I began using the pottery I made which led me to appreciate the experience of using pots. I have begun to have the same sense of appreciation for other things that I use such as clothes, shoes, bicycles, chairs, cars or anything else that I use for one function or another. I believe we live in a world that generally does not value our material culture, most things are cheap and disposable and I would like to create something that will add a small but valuable contribution to our shared material culture. I hope that this work will inspire a subtle shift in the way people think as consumers.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery